Exploring Gender and Academic Major Differences in Academic Self-Efficacy Among University Students in Xi’an, China - Liu, Yueqi; Dipolog-Ubanan, Genevieve (Journal of Education and Learning Environments, 2025)
This study examines the relationship between academic self-efficacy and academic performance among university students in Xi’an, China, while also exploring disparities in self-efficacy based on gender and academic major. Grounded in Bandura’s social cognitive theory, the research employs a quantitative, cross-sectional correlational design. A total of 389 undergraduate students from 29 universities were recruited through stratified random sampling. Data were collected using the College Academic Self-Efficacy Scale (CASES) and the Academic Performance Scale (APS) and analyzed using Pearson correlation and independent samples t-tests. The results reveal a moderate to strong positive correlation between academic self-efficacy and academic performance (r = 0.594, p < 0.001), indicating that students with higher self-efficacy tend to achieve better academic performance. Additionally, male students exhibited significantly higher self-efficacy levels than female students, and STEM students reported greater self-efficacy compared to non-STEM students. These findings highlight the role of academic self-efficacy in student success and suggest that universities should implement targeted interventions, such as mentorship programs and structured feedback mechanisms, to enhance self-efficacy. Addressing gender disparities and providing additional support for non-STEM students can further promote equity in higher education. Future research should consider longitudinal studies and additional contextual factors to deepen the understanding of self-efficacy development and its impact on academic performance.